EFFECT OF HEALTHY NUTRITION AND PHYSICAL ACTIVITY BEHAVIOR DEVELOPMENT PROGRAMS IN UNIVERSITY STUDENTS: A SYSTEMATIC REVIEW - DOST, Ayşe; ESİN, Melek Nihal (Göbeklitepe Medical Science Journal, 2021)
Objective: The aim of this study is to determine and systematically review the results of studies on the effects of health promotion programs applied to university students on healthy nutrition and physical activity behaviors. Method: In order to determine the impact of health promotion programs, the original intervention studies published by controlling the databases of Cochrane, Pubmed, Science Direct, Medline, SCOPUS, Ulakbim were examined. The survey was carried out in English using the keywords “university students and nutrition and exercise”, “university students and healthy eating and physical activity”, “university students and nutrition and physical activity”, university students and healthy eating and exercise”. A total of twelve articles that met the inclusion criteria of the study were evaluated. Results: The types of interventions made to university students are message, web-based education and group education via phone and e-mail. It was determined that the intervention was effective in 10 of the 11 studies included in the study among the interventions for university students. Conclusion and Suggestions: In most of the applied programs, an increase was observed in the healthy nutrition or physical activity levels of the students. The fact that interventions aimed at developing healthy nutrition and physical activity behaviors of university students are highly effective points to the necessity of determining cost-effective methods in future studies. Therefore, it is recommended that nurses plan university-based, multi-component interventions.